Enhancing FDI through Investment Policy Reform - World Bank (World Bank, Washington, DC, 2018)
The average annual FDI inflow in Bangladesh is significantly lower than comparable economies.Over the past decade (2007 to 2017), inflows have averaged at 0.9 percent of GDP in Bangladeshcompared with 3.0 percent in China, 5.5 percent in Ethiopia, 2.6 percent in The Philippines, 6.6 percent in Vietnam, 4.6 percent in Malaysia, and 2.1 percent in India. In 2017, the sectoral distribution of FDI was concentrated in businesses like telecom (24 percent), power and energy (20 percent), and banking and trading (11 percent). Inflows are primarily from the UK, USA, Norway, Singapore and South Korea which constitute about 65 percent of FDI inflows. The country’s export diversification strategy calls for an efficiency-seeking FDI policy regime with instruments for firm linkages, investment incentives, preferential trade agreements, and efficient services provided by investor promotion agencies (IPA). The absence of such a policy regime is one of the factors restraining FDI inflows into the country. FDI in Bangladesh is primarily reinvestment of retained earnings, reflecting investor confidence but also some constraints. More than 50 percent of FDI in Bangladesh are reinvestments. This shows confidence in the economy among the existing investors, However, the low levels of FDI and absence of new investors indicates problems related to greenfield entry barriers, valuation challenges, and repatriation restrictions. The dearth of enabling policies such as easy business entry, access to serviced land, and investor aftercare, limits the potential for investment in greenfield and expansion projects which are more likely to create new jobs.